Predictive Capability of Cardiopulmonary and Exercise Parameters From Day 1 to 6 Months After Acute Pulmonary Embolism - Dirk Habedank; Christian Opitz; Tim Karhausen; Thomas Kung; Ingo Steinke; Ralf Ewert (Clinical Medicine Insights: Circulatory, Respiratory and Pulmonary Medicine, 2018)
We hypothesized that the slope of relation ventilation to carbon dioxide output ( V’ E/ V’ CO2-slope) could be predictive already during the very first days after submassive pulmonary embolism (PE) to right ventricular systolic pressure (RV sys by echocardiography) after 6 months. We evaluated 21 hemodynamically stable patients at admittance, at days 3, 7, 90, and 180 by cardiopulmonary exercise testing and echocardiography. V’ E/ V’ CO2-slope (48.4 ± 10.8) decreased within the first week (43.0 ± 9.8 at day 7) and normalized until follow-up at 6 months (35.0 ± 11.3; P  < 10 -4 ), p(a-ET)CO 2 remained abnormal between days 1 and 3 (5.0 ± 3.9 to 6.7 ± 5.3 mmHg). RV sys declined from 41.7 ± 14.3 to 26.3±13.1 mmHg ( P  < 10 –4 ) at 6 months. V’ E/ V’ CO2-slope ( r ²= 0.27; P  < .02) and RV sys ( r ² = 0.28; P  = .03) at day 7 correlated with RV sys at 6 months. p (a-ET) CO 2 , p (a-ET) O 2 , V’ D/ V’ T were not related to RV sys after 6 months. RV sys 6 months after acute PE is positively correlated with the V’ E/ V’ CO2-slope at day 7.